Kajian Perubahan Aktivitas Dan Pemanfaatan Lahan Kampung Sukajadi Terkait Keberadaan Taman Wisata Lembah Hijau Bandar Lampung - Wiko Primadana; Bitta Pigawati (Jurusan Perencanaan Wilayah dan Kota, 2017)
Taman Wisata Lembah Hijau Kampung Sukajadi stood since year 2007 and conducive to tourist have an effect on to regional growth about. activity in Lembah Hijau really enough race growth of economic sector supporting tourism activity affecting farm exploiting and activity socialize Kampung Sukajadi, the change generate problem for Kampung Sukajadi area that is different farm exploiting and activity friction from previous function where Kampong Sukajadi representing rural area mostly its farm exploiting used as by a plantation area not yet can place farm exploiting and activity changing very fast effect of Lembah Hijau. This study aimed to assess changes in the activity and land use in Kampung Sukajadi related to the existence of Green Valley, Bandar Lampung. This study used quantitative descriptive and cross tabulation analysis (crosstab). Based on the results of the study, known changes in the activity of an increasing number of actors in the field of trade in services is quite high compared to the time before the existence of the Park Green Valley. While the plantation settlement activity and decreased the number of perpetrators of activity compared to the prior existence of these attractions. The highest land use changes that occurred in the village of Sukajadi related to the existence of the Park Green Valley namely plantation land use changes into land-use trade and service area of 11, 47 ha. Factors affecting changes in land use and activity that tourists jumla and service facilities.